Effects of fasting and intermittent fasting on rat hepatocarcinogenesis induced by diethylnitrosamine - Rocha, Noeme Sousa [UNESP]; Barbisan, L. F.; de Oliveira, MLC; de Camargo, JLV (Wiley-Blackwell, 2002)
The influences of fasting on DEN-initiation and of intermittent fasting (IF) on the rat liver chemical carcinogenesis process were evaluated in a 52-week long assay. Three groups of adult male Wistar rats were used: Groups I to 3 were treated with a single i.p. injection of 200 mg/kg of diethylnitrosamine (DEN). Group 2 was submitted to 48 h fasting prior to DEN treatment. After the 4th week, Group 3 was submitted to IF, established as 48 h weekly fasting during 48 weeks, while Groups I and 2 were fed ad libitum until the 52nd week. All animals were submitted to 70% partial hepatectomy and sacrificed at the 3rd and 52nd weeks, respectively. Fasting prior to DEN-initiation did not influence the development of altered foci of hepatocytes (AFHs) and of hepatic nodules (Group 2 vs. Group G1). IF inhibited the development of preneoplastic lesions, since this dietary regimen decreased the number and the size of glutathione S-transferase (GST-P) positive foci and the number and size of liver nodules (Group G3 vs. Group G1), the inhibitory effect of IF was also reflected in the development of clear and basophilic cell foci. These results indicate that long-term IF regimen exerts an anti-promoting effect on rat hepatocarcinogenesis induced by DEN. (C) 2002 Wiley-Liss, Inc.
Keywords: carcinogenesis; diethylnitrosamine; altered foci of hepatocytes; fasting; intermittent fasting